Isotopic niche partitioning of co-occurring large marine vertebrates around an Indian ocean tropical oceanic island. (January 2023) - Chandelier, Guillaume; Kiszka, Jeremy J.; Dulau-Drouot, Violaine; Jean, Claire; Poirout, Thomas; Estrade, Vanessa; Barret, Mathieu; Fayan, Jacques; Jaquemet, Sébastien
Abstract: Tropical oceans host a high diversity of species, including large marine consumers. In these oligotrophic ecosystems, oceanic islands often favour the aggregation of species and biomass as they provide feeding opportunities related to the mechanisms of island mass effect. As such, the waters surrounding La Reunion (Southwest Indian Ocean) host seabirds, large pelagic teleosts, elasmobranchs, delphinids and sea turtles. Isotopic niche partitioning and comparison of trophic levels among these species (n = 21) were investigated using stable carbon ( δ 13 C) and nitrogen ( δ 15 N) isotope analysis. Overall, δ 13 C values were highly variable among taxa, indicating that the species exploit multiple foraging habitats along a coast-open ocean gradient. Overlap in δ 15 N values was limited, except for teleost species, the two species of sea turtles and two species of delphinids, the Indo-pacific bottlenose dolphin ( Tursiops aduncus ) and the Spinner dolphin ( Stellena longirostris ). Stable isotope analyses of samples collected over a 9-years period on different tissues with different integration times provide a consistent picture of the structure of the community of large marine vertebrates species around La Reunion and highlight the underlying mechanisms to limit the competition between species. The wide range of isotopic values confirms that large marine vertebrates have different trophic roles in coastal marine food webs around this oceanic island, which limits their potential of competitive interactions for resources. Highlights: Off La Reunion large marine consumers have different trophic functions and strategies. δ 13 C analyses reveal that studied species forage along a coast-open ocean gradient. δ 15 N analyses suggest individual dietary-specialization especially in sea turtles. Overall the community of large consumers seems structured by the island mass effect.